Applying the Psychological of Space in Islamic Boarding School (Case Study: Pesantren Al Mahshyar Nurul Iman) - Reza Amalia Fitriani; Djoko Murdowo; Widyanesti Liritantri (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2023)
Adolescents have different psychological conditions and spend a lot of time in boarding schools because they must live in Islamic boarding schools where many rules and activities must be followed. The research method used in this case study is a qualitative method which consists of a survey, literature review, and data analysis. A spatial approach is taken to